Identification of detoxification pathways in plants that are regulated in response to treatment with organic compounds isolated from oil sands process-affected water. (November 2015) - Widdup, Ellen E.; Chatfield-Reed, Kate; Henry, Darren; Chua, Gordon; Samuel, Marcus A.; Muench, Douglas G.
Highlights: Transcript profiling of Arabidopsis plants exposed to the AEO fraction of OSPW. AEO treatment resulted in the upregulation of xenobiotic detoxification pathway genes. Several β-oxidation and stress responsive pathway genes were also activated. The AEO induced genes are targets for biosensing and phytoremediation strategies. Abstract: Bitumen mining in the Athabasca oil sands region of northern Alberta results in the accumulation of large volumes of oil sands process-affected water (OSPW). The acid-extractable organic (AEO) fraction of OSPW contains a variety of compounds, including naphthenic acids, aromatics, and sulfur- and nitrogen-containing compounds that are toxic to aquatic and terrestrial organisms. We have studied the effect of AEO treatment on the transcriptome of root and shoot tissues in seedlings of the model plant, Arabidopsis thaliana . Several genes encoding enzymes involved in the xenobiotic detoxification pathway were upregulated, including cytochrome P450s (CYPs), UDP-dependent glycosyltransferases (UGTs), glutathione-S-transferases (GSTs), and membrane transporters. In addition, gene products involved in oxidative stress, β-oxidation, and glucosinolate degradation were also upregulated, indicating other potential mechanisms of the adaptive response to AEO exposure. These results provide insight into the pathways that plants use to detoxify the organic acid component of OSPW. Moreover, this study advances our understanding of genes that could be exploited to potentially develop phytoremediation and biosensing strategies for AEO contaminants resulting from oil sands mining.